Identifikasi dan Enumerasi Escherichia coli dengan Kombinasi Metode MPN-PCR - Atik Kurniawati; Dwi Listyorini; Agung Witjoro (Universitas Muhammadiyah Surabaya, 2022)
Healthy and nutritious food should be free from biological contaminants. The presence of Escherichia coli in food is an indicator contamination and also presence of other pathogenic bacteria. This study aims to determine the value of MPN E. coli in food samples using the MPN-PCR combination technique. Descriptive research method. Samples were taken from 5 traders in Malang City. The results showed that 3 out of 5 food samples were contaminated with E. coli, indicated by the presence of a specific band amplified and produced a DNA band measuring 584 base pairs in agarose gel electrophoresis. Conclusion: MPN value of E. coli in the three food samples code II 34 MPN / gram, code III 75 MPN / gram and V code 290 MPN / gram. The MPN-PCR combination can be used as an alternative method for the conventional MPN test because it can detect the presence of E. coli bacteria in food quickly and reliably